SALES PROMOTION GIRL DI PEKANBARU (STUDI KASUS PADA PT. H.M SAMPOERNA Tbk,) - Andika Pramana Putra; Achmad Hidir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Sales Promotion Girl in Pekanbaru. This research was carried out ini Pekanbaru where researchers always visited places where there were ciggarette Sampoerna events. The purpose of this study is to find out what lies behind women who want to work as Sales Promotion Girl cigarettes and to find out what the joys and sorrows felt by women who work as Sales Promotion Girl cigarettes. The subjects in this study were five people namely those aged 24-26 years. The author uses qualitative methods and the data is analyzed qualitative and uses observational data collection techniques which include documentation and interviews. From the results of research conducted the authors found that the reason women work as Sales Promotion Girls is because of economic, the desire to live more independently. It can be concluded that the basic factor of women wanting to work as Sales Promotion Girls is because the economic needs that are increasingly increasing and the desire to live independently without burdening parents is also one of the factors women want to work as Sales Promotion Girls cigaretes in Pekanbaru. Keyword : Sales Promotion Girl